Wohlfahrtsschule der Innern Mission Danzig. (Danzig : [wydawca nieznany], 1928)
Druk informujący o szkole.
Keywords: Szkoły -- Polska -- Gdańsk -- 1900-1945 -- druki ulotne; Gdańsk (Polska) -- 1920-1939 (Wolne Miasto) -- druki ulotne; Wolne Miasto Gdańsk (1920-1939); Druki ulotne -- 1900-1945.; Druki ulotne